2007
DOI: 10.1093/sleep/30.12.1747
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Determination of Brain Tissue Oxygenation during Sleep in Obstructive Sleep Apnea: A Near-Infrared Spectroscopic Approach

Abstract: NIRS is an effective tool to evaluate brain tissue oxygenation in OSA. It provides valuable data in OSA assessment and has the potential to bridge current knowledge gap in OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 40 publications
(50 reference statements)
9
50
1
1
Order By: Relevance
“…By contrast reported changes of BV are more controversial. Several studies found BV to increase during apnea events 45,50 ; while other studies 41,42,44 including ours, showed that BV decreased, as shown in Figs. 1-3.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…By contrast reported changes of BV are more controversial. Several studies found BV to increase during apnea events 45,50 ; while other studies 41,42,44 including ours, showed that BV decreased, as shown in Figs. 1-3.…”
Section: Discussionsupporting
confidence: 46%
“…44 Olopade et al argued that the lower cerebral tissue oxygenation in OSA compared to control subjects may be related to the age disparity between the two groups. 42 Therefore, further studies with more patients are needed to clarify the patterns of changes of BV in OSA more thoroughly taking multiple factors into account such as age, body mass index (BMI), AHI or gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several clinical studies have measured the hemoglobin indices of OSAS patients during sleep using NIRS [6][7][8][9]. Except for Oropede's study, which showed a decrease in HbO and HbT during obstructive apnea episodes [8], all the study results [6,7,9], including our study, showed that HbO decreased during obstructive apnea episodes, while HbD, as well as HbT, reflecting CBV, showed adverse increases, and the values of these hemoglobin indices returned to the baseline value at the end of each apnea episode. Of note is that the results of Pizza et al [9] and our study revealed a positive correlation between the changes in peripheral SpO 2 and cerebral HbO during sleep in OSAS patients.…”
Section: Discussionmentioning
confidence: 99%
“…From changes in HbO and HbD within the tissue under observation, changes in oxygen delivery and consumption can be assessed, and from changes in total hemoglobin (HbT),which is the sum of HbO and HbD, changes in relative tissue blood volume can be measured in the absence of major changes in the hematocrit [5]. With regard to OSAS, several studies have evaluated the changes in these variables accompanied with apnea episode and/or hypopnea by using NIRS [6][7][8][9]. However, the relationship between the changes in percutaneal oxygen saturation (SpO 2 ) and brain tissue hemoglobin indices through respiratory events is still unclear.…”
Section: Introductionmentioning
confidence: 99%